2017
DOI: 10.5152/iao.2017.2745
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic Analysis of Used Tuning Forks

Abstract: OBJECTIVE:In this study, we evaluated used aluminum tuning forks (TFs) for fundamental frequencies (FF), overtones, and decay times. MATERIALS and METHODS:In total, 15 used (1 C1, 11 C2, and 3 C3) and 1 unused (C2) TFs were tuned, and the recorded sound data were analyzed using the Praat sound analysis program. RESULTS:It was found that FFs of the recorded sounds produced by the used C2-TFs presented a high variability from 0.19% to 74.15% from the assumed FFs, whereas this rate was smaller (1.49%) in the used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…31 Heavier materials have more sustained sound levels, and aluminum forks undergo metal fatigue, producing shorter decay times and performance deterioration over time. 32…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…31 Heavier materials have more sustained sound levels, and aluminum forks undergo metal fatigue, producing shorter decay times and performance deterioration over time. 32…”
Section: Discussionmentioning
confidence: 99%
“…A study that did not meet inclusion criteria (results of all fork frequencies were combined) reported greater accuracy with magnesium alloy forks over steel forks 31 . Heavier materials have more sustained sound levels, and aluminum forks undergo metal fatigue, producing shorter decay times and performance deterioration over time 32 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5 As a result, their fundamental frequency and decay times show differences up to approximately 74% and 41%, respectively. 7 Besides, Butskiy, Ng, Hodgson and Nunez published objective data supporting the classic recommendation about placingthe TFs parallel (PA) to the external ear canal (through the vibrating tinesof the fork), compared with the perpendicular (PE) placement. 8,9 They found that PA placement results in a higher sound energy at the level of the tympanic membrane.…”
mentioning
confidence: 99%